TRADITIONAL AND ETHNO-MEDICINAL KNOWLEDGE OF MUSHROOMS IN WEST BENGAL, INDIA - DUTTA, ARUN KUMAR; ACHARYA, KRISHNENDU (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Mushrooms are highly prized for their utilization as nutritional and medicinal foods. So, to meet the need of growing world's populations from the point of future food security, there is a recent craze among mycologists to document the nutritional and medicinal properties of mushrooms around the globe. However, in the Indian context, the attempts to unveil local folk use of mushrooms were meager. Therefore, the aim of this study was to assess the traditional knowledge of mushrooms among some local and indigenous communities (tribals) of eight districts of the state of West Bengal, India. A five-year (2008-2012) extensive survey explored altogether 34 macrofungi, among which 31 are used as food and the remaining for medicinal purposes in addition with some species which are used for both the purposes. The regional investigation showed that mushrooms being a non-timber forest product also provide a much-needed alternative source of income for rural households. Some species of Amanita, Astraeus, Russula, Termitomyces, Armillaria, Auricularia, Fistulina, Grifola, Hericeum, Coprinus, Pholiota, Meripilus, Pleurotus, Calocybe, Lentinus, Tricholoma and Volvariella are consumed as food. Species of Cordyceps, Ganoderma, Schizophyllum, Termitomyces etc. are used for medicinal purposes with various preparations. Powdered fruitbodies of Daldinia concentrica and Pisolithus arhizus are applied to skin for relief from burning, itching and healing minor skin infections after mixing with coconut (Cocos nucifera) oil. Keywords: India, medicinal foods, mushroom utilization, tribal communities